Effect of sugar on bread dough aeration during mixing. (April 2015) - Trinh, L.; Lowe, T.; Campbell, G.M.; Withers, P.J.; Martin, P.J.
Highlights: New fitting methodology enables dough aeration dynamics to be fitted with single parameter. Granulated sugar in bread dough increases the gas entrainment rate. Granulated sugar in bread dough increases the gas disentrainment coefficient. Relative increase in gas disentrainment coefficient is greater than entrainment rate. Dough aeration decreases with granulated sugar content. Abstract: The aim of this study was to understand better dough aeration and in particular to determine how aeration during mixing differs between sugar containing and non-sugar containing dough through modelling and X-ray tomography. Batches of non-yeasted bread dough were mixed using both 'plain' and 'strong' flours with systematically varying granulated caster sugar formulations. A modified Tweedy 1-type mixer was used and mixer headspace pressure was controlled at various constant values to determine steady state dough aeration conditions. Pressure step-change experiments were used to determine aeration dynamics. A population balance model was fitted to the data to enable quantitative determination of the gas entrainment rate and disentrainment coefficient. X-ray computed tomography studies and uniaxial extensibility tests were also conducted to explore further the results of the aeration studies. This method enabled the model to be fitted to the aeration step-change response using only one parameter. The main effects of granulated sugar in dough were to increase the disentrainment coefficient and, to a lesser extent, to increase the entrainment rate. The combined effect of these was a reduction in dough gas content as granulated sugar content increased.